2022
DOI: 10.3390/ijms23020788
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Trafficking and Signaling of the High Affinity IgE Receptor by FcεRIβ and the Potential Impact of FcεRIβ Splicing in Allergic Inflammation

Abstract: Mast cells are tissue-resident immune cells that function in both innate and adaptive immunity through the release of both preformed granule-stored mediators, and newly generated proinflammatory mediators that contribute to the generation of both the early and late phases of the allergic inflammatory response. Although mast cells can be activated by a vast array of mediators to contribute to homeostasis and pathophysiology in diverse settings and contexts, in this review, we will focus on the canonical setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 142 publications
(173 reference statements)
0
6
0
Order By: Relevance
“…102 FcεRIβ encodes a subunit of the high-affinity IgE receptor FcεRI and mediates trafficking and signaling of this receptor. 103 Meanwhile, ADAMTSL4 encodes a potential IgE-binding selfantigen in AD and has been linked to eosinophil counts, which are known to be elevated in AD. [104][105][106] Finally, CYSLTR1 encodes a receptor for cysteinyl leukotrienes; variants may predispose children to asthma and AD.…”
Section: Immune System Defects and Dysregulationmentioning
confidence: 99%
“…102 FcεRIβ encodes a subunit of the high-affinity IgE receptor FcεRI and mediates trafficking and signaling of this receptor. 103 Meanwhile, ADAMTSL4 encodes a potential IgE-binding selfantigen in AD and has been linked to eosinophil counts, which are known to be elevated in AD. [104][105][106] Finally, CYSLTR1 encodes a receptor for cysteinyl leukotrienes; variants may predispose children to asthma and AD.…”
Section: Immune System Defects and Dysregulationmentioning
confidence: 99%
“…Even though the stimulus-response coupling pathway has been well delineated for activation of the high-affinity surface receptor for IgE (FcεRI) [42,102,103], and, more recently, of the low-affinity receptor for cationic peptides, Mas-Related G Protein-Coupled Receptor-X2 (MRGPRX2) [104][105][106][107][108], there is still a lack of understanding of the molecular events regulating secretion, whether by degranulation, selective release of mediators or any other mode of secretion (Table 1). The mode and extent of mast cell responsiveness ultimately depend on the interplay between stimulatory and inhibitory signaling pathways, such as CD300 [109,110] and Singlets [111], especially Siglec-7 [112], and the β subunit of FcεRI (FcεRIβ) [113].…”
Section: Regulation Of Mediator Secretion From Mast Cellsmentioning
confidence: 99%
“…The FcεRI complex on human mast cell surface is a tetramer composed of one α subunit, one β-subunit, and 2 γ-subunits (αβγ2) [11,45,47]. Among these, the α-subunit has two extracellular Ig superfamily domains (α1 and α2), both of which are responsible for the ligand (Fc fragment of the IgE antibody) binding [10], while the β-and γ-subunits contain immunoreceptor tyrosine-based activation motifs (ITAMs) that provide binding sites for many intracellular signal molecules via their Sarcoma (SRC) homology 2 (SH2) domains [11,48,49].…”
Section: Structure and Synthesis Of The Fcεri Complexmentioning
confidence: 99%
“…Recent studies have shown that β-subunit hypofunction (by exon skipping) and hyperfunction (by an enhancer named MS4A4A) can either hamper or boost the development of allergic diseases, respectively [50,51]. Due to its core role, the FcεRIβ is a primary target of many therapeutic interventions for allergic diseases [49]. In addition, interaction of HDAC3 with a series of microRNAs can modulate the FcεRI activity and mediate passive anaphylaxis by deacetylating the histones [52].…”
Section: Structure and Synthesis Of The Fcεri Complexmentioning
confidence: 99%